PSYCHOLOGICAL MECHANISMS OF LEADERSHIP DEVELOPMENT IN MANAGERIAL PERSONALITY - Namozov Elbek (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the psychological mechanisms underlying the development of leadership abilities in managerial personalities. The study focuses on intrinsic motivation, emotional intelligence, cognitive processes, and social influence as key determinants of leadership effectiveness. A mixed-method approach was employed, including theoretical analysis, surveys, and psychodiagnostic assessments conducted among 120 managers. The findings reveal that leadership development is a multifaceted process shaped by the interaction of various psychological components. Emotional intelligence and intrinsic motivation were identified as the most significant predictors of effective leadership. The results emphasize the importance of implementing psychologically grounded leadership development programs in modern organizations.